Meningkatkan Keterampilan Proses Sains melalui Model Discovery Learning dengan Scientific Approach Siswa Kelas IX.I SMP Negeri 2 Mataram - Martedi, Didik (TSAQOFAH, 2023)
This classroom action research aims to: To find out the application of the discovery learning model with a scientific approach in learning science for class IX.I students of SMP Negeri 2 Mataram in the odd semester of the 2022/2023 academic year. To find out the increase in creativity and science learning outcomes through the application of the discovery learning model learning with a scientific approach for class IX.I students of SMP Negeri 2 Mataram in the odd semester of the 2022/2023 academic year. The research was carried out in two cycles where each cycle consisted of planning, action, observation, and reflection. The results of the descriptive analysis after the application of the discovery learning model with the scientific approach indicated that there was an increase in the value of science process skills that: Student activity in science learning with the Discovery Learning learning model with the Scientific Approach in cycle I was 70.24% (good enough category), then experienced increase in cycle II of 95.23% (very good category). Student learning outcomes in the initial conditions obtained an average of 80.26 or 64.10% classical completeness, to 84.33 or 82.05% classical completeness in cycle I, increasing to an average of 93.26 or 100% in cycle II. Based on these conclusions, the hypothesis that has been determined can be accepted, namely by applying the Discovery Learning learning model with a Scientific Approach can improve process skills and science learning outcomes for Class IX.I SMP Negeri 2 Mataram Odd Semester 2022/2023 Academic Year.